Pivotal trials of orthopedic surgical devices in the United States: predominance of two-arm non-inferiority designs - S. Raymond Golish (Trials, 2017)
Abstract Background The United States Food and Drug Administration (FDA) reviews class III orthopedic devices submitted for premarket approval with pivotal clinical trials. The purpose of this study was to determine the types of orthopedic devices reviewed, the design of their pivotal clinical trials, and the subjective factors affecting the interpretation of clinical trial data. Methods Meetings of the FDA Orthopaedic and Rehabilitation Devices Panel were identified from 2000–2016. Meeting materials were collected from FDA electronic archives and notes were made regarding the device-type and subsequent approval and recall, the design of pivotal clinical trials, and issues of trial interpretation debated during panel deliberations. Results The panel was convened on 29 separate occasions over the course of 35 days to deliberate 38 distinct topics. Of these, 23 topics included clinical data submitted for approval of a device, and two topics were excluded. Of the 23 devices, five were biologic, three were hip arthroplasty, three were disc arthroplasty, two were viscosupplementation, three were interspinous process devices, and seven were other devices. Of the 23 pivotal trials, 20 (87.0%) were randomized controlled trials (RCTs), consisting of 13 (65.0%) non-inferiority trials and 7 (35.0%) superiority trials, and all RCTs were two-arm trials. At panel, the most commonly debated issues were related to the design and interpretation of non-inferiority trials. Conclusions A broad array of device types is reviewed by the FDA. The predominance of two-arm non-inferiority trials as pivotal studies indicates that the nuances of their design and interpretation are commercially important.